lntrogression of Bacterial Leaf Blight Resistance Gene from Oryza Minuta J.B. Presl. Ex C. B. Presl. into New Rice Type (Oryza sativa L.) - Abdullah, Buang; Brar, D. S.; Carpena, A. L. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
F1 Hybrids, backcross progenies, advanced introgression lines (2n=24) and monosomic alien addition lines or MAALs (2n=25) were successfully produced following embryo rescue between an elite new plant type (NPT) breeding line of Oryza sativa (2n=24, AA) and a wild species, O. minuta (2n=48, BBCC). F1 hybrids performance were intermediate between the parents. The F1 hybrids had 36 chromosomes indicating having 12 chromosome A from O. sativa and 12 B and 12 C from O. minuta. THE BACK CROSS progenies had different chromosome number indicating abnormal meiosis of the hybrids and back cross progenies. Plant with 2n=24 and 25 chromosomes were obtained in BC4FI. The hybrids and backcross progenies were susceptible to bacterial leaf blight (BB). However, several of the 2n=24 plants derived resistant plant to bacterial leaf blight race 1 of the Philippines races. The gene is different from introgressed gene intio rice from O. longistaminata ( Xa21) and from O. Minuta Acc. 101141 I Key words: Oryza minuta, MAALS, Bacterial leaf blight